Gender Difference in the Coronary Risk Factors Amongst the Patients with Acute Coronary Events in Nepal - Raut, Bharat; Vaidya, Abhinav; Gurung, Jessen; Acharya, Subhash; Basnet, Pravesh; Sodhi, H.S.; Karki, Dambar Bahadur; Jha, Sunil Chandra (Nepalese Heart Journal, 2019)
Background: Acute Coronary Event (ACE) is the commonest cause of admission in Coronary Care Unit (CCU) in Nepal. With growing epidemic of coronary artery disease in Asian countries, there is an urgent need to assess the locally prevalent coronary risk factors. There seems to be a significant difference in the risk factors amongst male and female population.Methods: A prospective analysis was done in 404 consecutive patients admitted with an acute coronary event in CCU in the Norvic Escorts Health Care And Research Centre, Kathmandu from January 1999 to July 2002. The data was analyzed and various risk factors were stratified.Results: Out of 404 patients of ACE, 251 (62%) patients were males and 153 (38%) patients were females. The commonest risk factors amongst male patients were smoking in 160 (64%), hypertension in 148 (59%) and dyslipidemia in 133(53%), followed by diabetes in 80 (32%) and a positive family history in 65 (26%) patients. As against this, female patients had commonest risk factors as hypertension in 71 (47%), diabetes in 71 (47%) and smoking in 64 (42%), followed by a positive family history in 47 (31%), and dyslipidemia in 23 (15%) patients.Conclusions: Smoking is the most common risk factor followed by Hypertension and Dyslipidemia in male patients with ACE, but most female patients with ACE have Hypertension as the most common coronary risk factor followed by diabetes mellitus. This may be partly due to the difference of socio-economic status of two genders in Nepal. An aggressive preventive approach is mandatory to decrease the expensive burden of coronary artery disease in this poor Himalayan country.